Programa psicoeducativo basado en el arteterapia para mejorar las relaciones de afectividad en estudiantes de educación básica del barrio Zarzas ii de la ciudad de Loja, periodo agosto 2020- febrero 2021. - González Molina, Mayrovi Alejandra (2021)
The research work entitled PSYCHOEDUCATIONAL PROGRAM BASED ON RTETHERAPYTO IMPROVE AFFECTIVITY RELATIONSHIPS IN STUDENTS FROM BASIC EDUCATION OF THE ZARZAS II NEIGHBORHOOD OF THE CITY OF LOJA, PERIOD AUGUST 2020- FEBRUARY 2021, had as a general objective the implementation of art therapy as a psychoeducational strategy to improve psychoeducational strategy. Affectivity relationships in basic education students, for which the non-experimental methodology was applied, the methods used were: scientific and inductive for The search and analysis of reliable scientific information, as an instrument, the Affective Balance scale was applied to 10 students of Basic Education of Barrio Zarzas II, which measures the type of affectivity that students have, among the main results it was determined that the 70% of the investigated population has a type of negative affect and 30% have a positive affect. Among the conclusions, it is evident that through the application of the Affective Balance scale, it was possible to diagnose the type of positive and negative affect in basic education students, for which it is recommended that the directors of the educational institutions of the Zarzas II neighborhood implement the psychoeducational program based on art therapy to improve affective relationships in basic education students